Logical-mathematical thinking in teachers of secondary education: an ethnomathematical perspective - Adalberto Lucas Cabello, Arturo Lucas Cabello, Eva Mizpa Isidro Natera, Rocío Del Pilar Davila Soto, Cesar Lincoln Gonzales Soto (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the research was to identify the relationship between the development of logical-mathematical thinking and ethnomathematics as pedagogical resources in teachers of secondary. A research with a quantitative approach, quasi-experimental design, and explicative level was carried out. Also, a non-probability sampling was carried out to choose 60 teachers of secondary of two educational institutions of the city of Lima, Peru. A methodology with pre and post-test was applied to an experimental group and control groups, using a test of mathematical skills as an instrument of data collection. The experimental group was intervened through the application of six topics related to the fundamental mathematical operations under an ethnomathematical approach. The results were analyzed through a descriptive statistic and a variance analysis, with a reliability level of 95 %. The intervention, carried out under the ethnomathematical approach, influences the increase of skills of logical-mathematical thinking in a significant way in comparison with the level shown at the beginning of the research.